2023
DOI: 10.15252/embj.2022113348
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐EM structure of the chain‐elongating E3 ubiquitin ligase UBR5

Abstract: UBR5 is a nuclear E3 ligase that ubiquitinates a vast range of substrates for proteasomal degradation. This HECT domain‐containing ubiquitin ligase has recently been identified as an important regulator of oncogenes, e.g., MYC, but little is known about its structure or mechanisms of substrate engagement and ubiquitination. Here, we present the cryo‐EM structure of human UBR5, revealing an α‐solenoid scaffold with numerous protein–protein interacting motifs, assembled into an antiparallel dimer that adopts fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Helical-repeat platforms also recur in the structures of UBR5 (refs. 10 , 11 , 47 , 48 , 50 ), Ufd4 (ref. 49 ) and AF2 predictions of additional human HECTs, such as HECTD1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helical-repeat platforms also recur in the structures of UBR5 (refs. 10 , 11 , 47 , 48 , 50 ), Ufd4 (ref. 49 ) and AF2 predictions of additional human HECTs, such as HECTD1.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 ) and UBR5 (refs. 10 , 11 , 47 , 48 , 50 ). The dynamic nature of these regions may allow HECTs to recruit diverse substrates for modification within the constraints of an overall similar catalytic platform.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this idea, recent structural studies of HUWE1 have revealed three distinct substrate binding domains 106,107 , facilitating the recognition and ubiquitination of unbound nucleic acid binding proteins as well as ubiquitinated/PARylated substrates. Similarly, UBR5 was recently shown to bind and ubiquitinate unengaged transcription factors 87 , and has the ability to function as a ubiquitin chain elongating E4 90,91 . In combination with our findings in this study, these results indicate that HUWE1 and UBR5 are both important players in recognizing and degrading unengaged DNA- and RNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also observed clear differential recognition, such as MLLE PABC1 and MLLE UBR5 binding to PAM2 GW182 and PAM2L MKRN1 , respectively. Recent cryo-EM structural analyses revealed that UBR5 forms functional dimers and tetramers (27,28). Interestingly, MLLE UBR5 is inserted in the middle of the catalytic HECT domain essential for ubiquitin transfer (Fig.…”
Section: The Slim-based Mlle Domain Binding Codementioning
confidence: 99%
“…This domain interacts with PAM2 sequences such as PAM2 PAIP , with high affinity (25). However, the biological function of its MLLE domain is currently unclear (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%